Texto publicitário e universo persuasivo: um olhar enunciativo para o slogan - Malossi, Tailor Roberto (2017)
Persuasion, as a constituent element in human interaction and present in all cultures, is explored in various forms in the advertising genre, especially in slogans. This genre, whose text is easily memorized, consists of a repetitive expression of an idea or purpose that extols the characteristics of a product, idea, service, person, in a commercial, political, religious context. This study is justified by the diversified action of the slogan in the social environment, influencing the behavior of citizens of different age groups and cultures. The general objective of this dissertation is to analyze the slogan in the publicity text, taking as a theoretical basis the linguistics of enunciation of Émile Benveniste, in order to establish the interlocution relations between an I and a Thou, identifying the linguistic marks that denounce the persuasion. In relation to the hypotheses raised, it is worth noting, first, that the resource of persuasion occurs fundamentally through the word, through argumentative resources and, above all, in a relationship that is always intersubjective. Language, according to Benveniste, means, and this is its primordial characteristic, its original vocation that transcends and explains all the functions that it ensures in the human environment. Well before serving to communicate, language serves to live and without it, there would be neither possibility of society nor possibility of humanity. The corpus is formed by five slogans whose methodology directs the analytic work to enunciative interpretations of this genre. It is in the intersubjective relationship of tongue and language that the persuasive effect is consolidated. Although the publicity text implies multiple analyzes, considering its dual constitutive nature of language - verbal and nonverbal -, it is by appropriating the whole language to state that the subject constructs always singular meanings. More than conceiving the slogan as a text, it is necessary to unveil this statement in discursive practice, that is, as a manifestation that articulates and references the categories of person (I / you), time (now) and space (here), even if they are presented in an implicit form. The results of this study show that it is in the appropriation of language by the subject, in the inseparable relationship between form and meaning, in the subjectivity, that persuasion is constructed in and by enunciation.